The Impact of Pulmonary Rehabilitation on Advanced Stage Lung Cancer Patients Receiving Chemotherapy or Radiotherapy: A Systematic Review and Meta-analysis - Putri, Yelsa Yulanda; Suyastri, Suyastri; Maryani, Siti (Majalah Kedokteran Andalas, 2025)
Objective: This study aims to analyze the efficacy of pulmonary rehabilitation on exercise capacity, lung function, and quality of life (QoL) in advanced lung cancer. Method: This Systematic Review and meta-analysis were conducted based on Randomized Clinical Trials and Prospective articles obtained through searches in PubMed, Google Scholar, Europe PMC, and Cochrane Library. The review focuses on the predetermined topic. The quality of the study was assessed by the Jadad scale for clinical trial studies and Newcastle Ottawa Scale for Cohort. Statistical analysis was done using Review Manager 5.4 software. Result: A total of 6 RCT studies with 251 participants were included in this metaâ€analysis. Patients with lung cancer who have received chemotherapy and or radiation therapy and undergo pulmonary rehabilitation programs have a significant impact on exercise capacity The Six Minute Walk Test (MD=72.06Â  [95% CI 25.45, 118.67], p=0.002), Forced Expiratory Volume (MD=13.03 [95% CI 0.18,25.89], p= 0.05), Forced Vital Capacity (MD=12.44 [95% CI 0.58, 24.30], p= 0.04) dan HRQoL Functional Assessment of Cancer Therapy-Lung Cancer Subscale (MD=1.64Â  [95% CI 0.07,3.21], p= 0.04). Conclusion: Our study suggests that pulmonary rehabilitation impact exercise capacity (6MWT), improvement in lung function, and quality of life.Keywords: Lung cancer; Pulmonary Rehabilitation; Chemotherapy; Radiotherapy